Genetic Characteristics of Multiparous Goats according to the Loci of Some Polymorphous Proteins in Blood and Milk - Badalyan, M. V.; Marmaryan, Yu. G.; Navasardyan, D. S.; Kharatyan, S. A. (ՀԱԱՀ հիմնադրամ)
The issues related to the study of multiparity in agricultural animals as a prior biological property, and those to making it more manageable were raised in the scientific research field still at the beginning of previous century. To solve the mentioned issues multiple approaches and hypotheses were drawn forward in different periods, but they were very often mutually exclusive. The article considers the genetic characteristic of multiparous goats per the loci of some polymorphous proteins in the blood and milk with the aim of applying the detected genetic markers in the selection process of the branch.
Keywords: Veterinary Science and Animal Breeding